2022
DOI: 10.1038/s41598-022-12086-8
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of bee pollen in acute kidney injury, proteinuria, and crystalluria induced by ethylene glycol ingestion in rats

Abstract: Oxidative stress plays a role in hyperoxaluria-induced kidney injury and crystallization. Bee pollen is a hive product with a high content of antioxidants. The antioxidant content and protective effect of bee pollen extract (BPE) against ethylene glycol (EG) induced crystalluria, and acute kidney injury (AKI) were investigated. The effect of BPE on the EG-induced liver injury and proteinuria was also examined. Ten groups of male Wister rats were treated daily with vehicle, cystone, BPE (100, 250, and 500 mg/kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Histopathological studies of the liver and kidneys showed an improvement in cellular architecture after propolis therapy and confirmed its hepatoprotective efficacy [46] . Bee pollen reduces proteinuria and prevents ethylene glycol‐induced acute kidney injury, crystalluria, liver injury, and histopathological changes in kidney tissue [47] …”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Histopathological studies of the liver and kidneys showed an improvement in cellular architecture after propolis therapy and confirmed its hepatoprotective efficacy [46] . Bee pollen reduces proteinuria and prevents ethylene glycol‐induced acute kidney injury, crystalluria, liver injury, and histopathological changes in kidney tissue [47] …”
Section: Discussionmentioning
confidence: 66%
“…[46] Bee pollen reduces proteinuria and prevents ethylene glycol-induced acute kidney injury, crystalluria, liver injury, and histopathological changes in kidney tissue. [47]…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies of BP extracts obtained by diverse solvents, including ethanolic [ 148 , 156 , 167 , 168 ], hydroethanolic [ 15 , 154 , 171 , 179 ], and diverse organic solvent-mediated extracts [ 150 , 151 , 153 , 175 ], have noted important antioxidant activities regardless of the extraction media. These bioeffects were also widely reported in animal models by studies that focused on different anatomical organs and physiological systems including renal [ 174 ], nervous [ 139 , 174 ], digestive [ 144 , 151 ], and reproductive [ 172 , 185 ] systems, as well as on different biochemical, hematological, and toxicological markers at systemic levels [ 137 , 165 , 184 ].…”
Section: Resultsmentioning
confidence: 90%
“…When related to the compound class of mangrove fruit artificial coffee detected by GC-MS analysis, previous studies have reported antioxidant compounds of the fatty aldehyde class can provide protective effects against oxidative stress-related damage in the renal (Zhang et al, 2021). The phenolic aldehyde-like class of compounds from bee pollen extract was reported to exert protective effects against histological changes in the renal, including crystal deposition, collecting tubule dilatation, tubular epithelial necrosis, inflammation, edema, and interstitium congestion (Elghouizi et al, 2022). The fatty acid class of compounds was also reported to attenuate toxicity in the renal by modulating oxidative stress and cell apoptosis (Elsafty et al, 2023).…”
Section: Resultsmentioning
confidence: 99%